Maternally Expressed Gene 3 (MEG3) Enhances PC12 Cell Hypoxia Injury by Targeting MiR-147 - Han, Lili; Dong, Zhiling; Liu, Ningning; Xie, Fei; Wang, Ning (Cellular physiology and biochemistry, 2017)
Background/Aims: Cerebral ischemia often leads to breakdown of blood–brain barrier (BBB) and vasogenic edema. It remains to be established whether MEG3 is responsible for the hypoxic damage in neural cells. This study aimed to investigate the role of MEG3 in the hypoxia-induced injuries of PC12 cells. Methods: The PC12 cells were seeded and cultured under hypoxia and normoxia culture conditions. The cell viability determined by trypan blue exclusion, apoptosis using propidium iodide (PI) and fluorescein isothiocynate (FITC)-conjugated Annexin V staining, cell-migration using a modified two-chamber migration assay with a pore size of 8 µM and invasion using 24-well Millicell Hanging Cell Culture inserts with 8 µM PET membranes. Results: Cell viability, relative migration and relative invasion decreased significantly in PC12 cells injured due to hypoxia as compared to control cells. An increase in apoptosis was also observed. The expression of MEG3 was up-regulated in hypoxia-injured PC12 cells. MEG3 overexpression enhanced hypoxia injuries, while MEG3 suppression attenuated the injuries. Meanwhile, MEG3 negatively regulated miR-147 expression. In addition, we found that the expression of Sox2 was increased in PC12 cells after hypoxia and miR-147 negatively regulated Sox2 expression through targets its 3’-UTR. Interesting, Sox2 activated NF-κB pathway and Wnt/β-catenin pathway in PC12 cells. Conclusion: Considering the observations in our study, we can conclude that MEG3 aggravated the hypoxial injury in PC12 cells by down-regulating miR-147 gene and miR-147 further negatively regulated Sox2 expression.